Comparative Evaluations of Selected Pigeon Pea (Cajanus cajan) Genotypes for Biomass Yield, Nutrient Composition, and Dry Matter Intake under Diverse Locations of Tropical Africa - Abuye Tulu; Mekonnen Diribsa; Gutu Fekede; Worku Temesgen; Wakgari Keba; Alemayehu Kumsa (Advances in Agriculture)
Feeding standards of ruminant livestock could be significantly enhanced through the cultivation of improved quality forages, which are suitable for different agroclimatic conditions in tropical Africa. In this frame, ten pigeon pea (Cajanus cajan) genotypes were evaluated across three locations in western Ethiopia during the 2014 and 2015 cropping seasons using a randomized complete block design with three replications. The study was designed to determine the nutrient composition, in vitro digestibility, and dry matter intake of selected pigeon pea genotypes. The result revealed that the studied quality parameters were significantly influenced by the genotypic and environmental main effects but not their interaction, while forage yield was influenced by both main effects and their interaction. Mean forage yield was greater for Degagsa across all locations followed by Belabas. In vitro organic matter digestibility and ash parameters did not vary among genotypes. However, variations were observed across locations for daily dry matter intake (DMI) and crude protein (CP) with the greatest value received from Degagsa and Belabas. The fiber components of Degagsa and Belabas were less than those of the remaining genotypes. Generally, Degagsa and Belabas had shown a greater forage yield, DMI, and CP content, but less in fiber components, and thus can be cultivated to enhance livestock productivity in western Ethiopia and similar agroecologies of tropical Africa.